Visibilidad de la divulgación científica de los profesores de las carreras de Comunicación de la Universidad Nacional de Loja, Universidad Técnica Particular de Loja y Universidad de Cuenca y su impacto en las plataformas digitales Academia.edu y Google Academic en el período junio 2022 – junio 2023. - Ordoñez Castillo, Gabriel Andrés (2024)
This research focused on comparing the visibility of scientific dissemination of the Universidad Nacional de Loja, Universidad Técnica Particular de Loja and Universidad de Cuenca and its impact on the digital platforms Academia.edu and Google Academic in the period June 2022 - June 2023, which allowed identifying the channels of visibility of scientific dissemination of professors of the Communication careers of the Universidad Nacional de Loja, Universidad Técnica Particular de Loja and Universidad de Cuenca. The methodology used was web observation, and it was carried out under a mixed approach, with its respective research technique, observation; and its instrument, the observation table. The results obtained allowed concluding under analysis. This inquiry allowed the generation of graphs that represent the percentage of teachers' preferences regarding the choice of platforms for their publications, as well as the difficulties they encounter in this process and the recommendations they may have in this regard. Keywords: Scientific dissemination; Communication; academia; Google Academic; Academia.edu.